How Do Treasury Systems Operate in Sub-Saharan Francophone Africa? - Leruth, Luc (IMF Working Papers; Working Paper ;, 2002)
Treasury systems in sub-Saharan francophone African countries share many features with the French public expenditure management system of the sixties on which they were modeled. However, in a different economic and institutional environment, key elements of this framework have evolved in unexpected, unwelcome directions. This paper critically examines two main features of the French system in the sub-Saharan francophone African context: the strict separation between the person ordering payment and the one disbursing funds, and the centralization of funds in the treasury. This examination calls attention to-and suggests remedies for-the specific flaws that have evolved from the traditional framework.